Sistematic Review: Relationship between Pregnant Women Weight, Fetal Weight, Age at Pregnancy, Gravida Status with Birth Weight - Liliek Pratiwi (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2020)
Background : A person's nutritional condition is influenced by her nutritional status during the womb. In other words, the nutritional status of pregnant women is very influential on their own health and as a predictor of pregnancy outcomes for mothers and nutritional status of newborns (Senbanjo et al, 2013). This is due to fetal food intake can be through the umbilical cord that is connected to the mother's body (Indreswari et al, 2008). Various maternal and child health efforts are carried out to reduce mortality. One of them is obstructed fetal growth which must be known while still in utero so that the clinician can be more stringent in monitoring and planning the delivery method to reduce the risk of perinatal death. The increase in maternal weight during pregnancy is directly related to the weight of the baby and the risk of giving birth to low birth weight increases with a lack of weight gain during pregnancy. This shows a significant relationship between the increase in body weight of pregnant women and the weight of the baby born. (handayani, 2013). From several studies, it is still not known what factors most influence the birth weight of the baby, so in this study sistematic review was carried out as a strong first step for other researchers in developing this research. Method : A systematic review through journal reviews of the relationship between maternal weight, fetal weight, age at pregnancy, status of Gravida with birth weight Result and Discussion : Based on the analysis of the article it was found that the relationship between maternal weight, fetal weight, gestational age, gravida status and birth weight. Several studies have reported an increased risk of low birth weight (LBW) among offspring (generally defined as women <20 years). The number of births for women 35 years and over is increasing in both high-income countries and middle-income countries. Several mechanisms have been suggested to explain this. Biological mechanisms for increasing infant birth Low birth weight (LBW) in teenage mothers <20 years can be explained as follows. Blood circulation to the cervix and also to the uterus in adolescents is still not perfect so this can interfere with the process of channeling nutrients from the mother to the fetus she contains. Nutrition of pregnant adolescents also plays a role because adolescents still need nutrients to be shared with the fetus they contain compared to adult pregnant women who do not need nutrients for growth (Johanes, 2009 in Rahardjo et al, 2011). Teenage mothers are inherently at risk for birth outcomes that are compromised because biological factors are considered. A large US sample shows that unfavorable birth outcomes for adolescent mothers compared to older mothers occur at several levels due to biological factors (Fraser, Brockert, & Ward, 1995; Chen, et al., 2007). However, additional research shows that this difference does not exist among African-American women because of higher average exposure to social and environmental losses compared to whites (Geronimus, 1987; 1996). This explanation shows that unfavorable birth outcomes among teens compared to older mothers are the norm, from which African American mothers deviate as a result of lower socioeconomic status (SES). The role of social loss in understanding the risks of compromised young mothers from birth outcomes is examined, especially those related to the selection of disadvantaged teenagers to give birth to children. Thus, the way the age of young mothers is associated with unfavorable birth outcomes is considered, both cross and in racial / ethnic groups Conclusion : This study has not been able to find a relationship between the weight gain of pregnant women on the weight of the baby born. According to assumptions, this happens because there are still other factors that are not yet known exactly where these factors can affect the weight of the baby born.